Anti-Bacterial And Anti-Ultraviolet Activity Test Of Black Cucumber (Holothuria atra) Extract From Tongkaina Waters, Bunaken District, Manado City - Mangangkung, Nazarrian; Angkouw, Esther Dellayani; Warouw, Veibe; Mangindaan, Remy Emile Petrus; Losung, Fitje; Monijung, Revol Dulles (Sam Ratulangi University, 2023)
The purpose of this study was to obtain the crude extract of Holothuria atra, test its antibacterial activity against Escherichia coli and Bacillus megaterium strains using the disc diffusion method (Kirby-Bauer disc diffusion), test the anti-UV of Holothuria atra extract taken from Tongkaina Waters, Bunaken District, Manado City. Antibacterial testing was carried out with several different concentrations, from the results of antibacterial testing carried out the average inhibition zone on E. coli bacteria with 100,000 ppm the average inhibition zone was (9.67 mm), for 50,000 ppm the average inhibition zone was (8 mm), from B. megaterium bacteria known to have H.a 100,000 ppm producing an average inhibition zone (9.67 mm), H.a 50,000 ppm an average inhibition zone of (8.67 mm). The results of the anti-UV test for Holothuria atra extract showed absorption in UV-C at λ 210 nm with the highest absorbance value of 2.774. Keywords: Sea cucumber, Antibacterial, Anti-UV, Escherichia coli, Bacillus megaterium. Abstrak Tujuan dari penelitian ini untuk mendapatkan ekstrak kasar Holothuria atra, menguji aktivitas antibakteri terhadap strain Escherichia coli dan Bacillus megaterium dengan metode difusi agar (disc diffusion Kirby-Bauer), menguji anti-UV dari ekstrak Holothuria atra yang diambil dari Perairan Tongkaina Kecamatan Bunaken Kota Manado. Pengujian antibakteri dilakukan dengan beberapa konsentrasi yang berbeda, dari hasil pengujian antibakteri yang dilakukan rerata zona hambat pada bakteri E. coli dengan 100.000 ppm rerata zona hambat sebesar (9,67 mm), untuk 50.000 ppm rerata zona hambat sebesar (8 mm), dari bakteri B. Megaterium diketahui H.a 100.000 ppm menghasilkan rerata zona hambat (9,67 mm), H.a 50.000 ppm rerata zona hambat sebesar (8,67 mm). Untuk hasil pengujian anti-UV ekstrak Holothuria atra menunjukkan serapan pada UV-C pada λ 210 nm dengan nilai absorban tertinggi 2,774. Kata kunci : Teripang laut, antibakteri, anti-UV, Escherichia coli, Bacillus megaterium.